2013
DOI: 10.1177/0146167213483580
|View full text |Cite
|
Sign up to set email alerts
|

Are Narcissists Sexy? Zeroing in on the Effect of Narcissism on Short-Term Mate Appeal

Abstract: This research was aimed to provide a comprehensive test of the classic notion that narcissistic individuals are appealing as short-term romantic or sexual partners. In three studies, we tested the hypotheses that narcissism exerts a positive effect on an individual's mate appeal and that this effect is mediated by high physical attractiveness and high social boldness. We implemented a multimethod approach and used ratings of opposite sex persons (Study 1), ratings of friends (Study 2), and records of courtship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(83 citation statements)
references
References 56 publications
7
73
2
Order By: Relevance
“…The finding that the effect was stronger for admiration than for rivalry might be explained by the fact that admiration entails to a greater degree the charming and entertaining aspects of narcissism (Back et al, 2013;Dufner et al, 2013;Dufner et al, 2015). However, in Study 2, we found only weak relationships between sensation seeking and affiliation with mates high in admiration or rivalry.…”
Section: 1sensation Seekingcontrasting
confidence: 64%
See 1 more Smart Citation
“…The finding that the effect was stronger for admiration than for rivalry might be explained by the fact that admiration entails to a greater degree the charming and entertaining aspects of narcissism (Back et al, 2013;Dufner et al, 2013;Dufner et al, 2015). However, in Study 2, we found only weak relationships between sensation seeking and affiliation with mates high in admiration or rivalry.…”
Section: 1sensation Seekingcontrasting
confidence: 64%
“…Past research has found that individuals' level of narcissism 1 is positively associated with their mate appeal and their success in initiating contact to potential romantic or sexual partners (Dufner, Rauthmann, Czarna, & Denissen, 2013;Holtzman & Strube, 2011). In this context, physical attractiveness-which appears to be explained by narcissists' tendency to wear fancy clothes and adornments-is one driving force behind narcissists' appeal for romantic affairs or short-term relationships (Holtzman & Strube, 2010, 2013Vazire, Naumann, Rentfrow, & Gosling, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Some of this research has focussed on mate choice for the Dark Triad characteristics, suggesting that the traits may either be aversive or desirable, depending on the mating context, methodology of the studies, and characteristics of the rater (e.g., Aitken, Lyons, & Jonason, 2013;Carter, Campbell, & Muncer, 2014;Dufner, Rauthmann, Czarna, & Denissen, 2013;Lyons, Marcinkowska, Helle, & McGrath, 2015;Rauthmann & Kolar, 2013). However, less is known about the Dark Triad in the context of assortative mating, especially during initial mate attraction.…”
Section: Introductionmentioning
confidence: 99%
“…Narcissistic behaviors, too, are reported to increase attractiveness, especially as a short-term romantic or sexual partner (174).…”
Section: Behaviors and Attitudesmentioning
confidence: 99%